Enhancing Independence and Learning Motivation by Using Youtube - Ayu Riyanti, Galuh; Hartono, Hartono; Marwoto, Putut (Universitas Negeri Semarang, 2019)
Independence is the ability to stand alone, work and carry out activities well, the students' independence often appears including cheating, copying their friends work and much more. Motivation is a basic impulse that moves students to do something, this motivation is related to student involvement in activities in the classroom, such as the urge to do something based on certain goals. This research is an effort to improve student independence and motivation through the use of youtube videos. The result of data analysis shows that the use of youtube videos can increase independence, motivation to learn, physics learning outcomes and the ability to use measuring instruments in tenth grade of mechanical engineering, SMK Nusantara 1 Comal. The use of learning models with the help of Youtube videos can enable students to work on assigments which further can ultimately improve their learning outcomes.